Rethinking foreign policy - Bynander, Fredrik.; Guzzini, Stefano. (Routledge advances in international relations and global politics ;, 2013)
"This edited volume is a tribute to, and a debate with, the scholarship of Walter Carlsnaes and his contribution to the study of foreign policy in both its conceptualization and application.This book probes the theoretical boundaries of Foreign policy analysis, and questions orthodox understandings of the field. It examines the Agency-Structure debate, the question of how human decision-making affects the norms and institutions of international interactions (and vice versa), and analyses how the study of Foreign Policy can be applied to the European Union as a supranational entity devoid of traditional statehood. Contributors offer an in-depth discussion on the intricacies of studying foreign policy, and provide new perspectives on the standing of the EU as a foreign policy entity.Rethinking Foreign Policy will be of interest to students and scholars of International Relations, Foreign Policy, Global Governance, EU studies, and the work of Walter Carlsnaes"--